Fatores relacionados à gravidade da doença periodontal em cães - Mariano, Kauana Peixoto (2013)
Periodontal disease is characterized by inflammation and destruction of periodontal structures. It is a disease that most commonly affects dogs, its agent is the accumulated plaque on surface. The aim of this study was to evaluate the influence of mixed and dry homemade diets, age and body score, the severity of periodontal disease in 73 dogs. We performed nutritional assessment, oral cavity clinical examination and laboratory tests, as well as a survey, in which the owners were interviewed and filled out a questionnaire on the dietary habits of their animals. The severity of periodontal disease increased with ageing of the animal. Body condition score was negatively correlated with the severity of disease, thus animals with more severe periodontal disease had lower scores. The type of food given to the dogs showed no correlation with the severity of periodontal disease.